Unbroken: Stories of Strength, Solidarity, and Resistance from Canadian Federal Prisons Designated for Women - Fayter, Rachel (Université d'Ottawa | University of Ottawa, 2025)
Historically, criminology has taken a deficit-focused or risk and needs-based approach to examining criminological issues (Kewley, 2017). Additionally, criminology has done little to explore how engaging in positive experiences can support criminalized people and prevent further conflict with the law (Ronel & Eisha, 2011). “Correctional” programming and policies employ a psychological lens, portraying women as having disordered thinking, irrational behaviours, personality disorders, along with many risk factors and needs that require “fixing” (Pollack, 2004). In response, there has been a proliferation of critical literature documenting incarcerated women’s harmful coping strategies in reaction to structural oppression and interpersonal harms, such as self-harm, suicide, eating disorders, and substance abuse (e.g., Chamberlen, 2018; Kilty, 2011, 2012, 2014; Moore & Scraton, 2014; Zinger, 2019). Less is known about incarcerated women’s strengths, skills, solidarity, resistance, and resilience. This project provides a more wholistic understanding of incarcerated women and gender-diverse people’s identities by challenging the prevalence of deficit-focused narratives and demonstrating the characteristics of resilient prisoners. A strength-based conceptual framework of prisoner resilience, linked to central features of healing and transformative justice, was developed to guide data collection and analysis. Mobilizing feminist, qualitative, and autoethnographic research methods within the critical paradigm, interviews were conducted with 13 key informants and 20 people who were incarcerated in federal prisons designated for women. Data were interpreted via thematic narrative analysis. This study’s findings reveal that promoting criminalized people’s strengths and fostering prisoner resilience can buffer the impact of the harmful conditions of confinement, support community re-entry, and contribute to transformative social change. The harms of the carceral state are severe and extensive, leading to further exclusion of some of the most marginalized people in society. Rather than interventions targeting the perceived deficits and needs of criminalized people, a strengths-based approach that promotes healing, resilience, and relational connections is needed to build safe, inclusive, caring communities.
Keywords: Gendered confinement; Strength-based Re-entry; Resilience; Resistance; Solidarity; Transformative Justice